Evgeny Nikolaevich Sedov: a leading breeder of pome fruit crops in Russia - A. M. Galasheva; Т. V. Yanchuk; N. G. Krasova (Труды по прикладной ботанике, генетике и селекции)
Acad. Evgeny Nikolaevich Sedov, Doctor of Agricultural Sciences, Full Member of the Russian Academy of Agricultural Sciences, Full Member of the Russian Academy of Sciences, Professor, Scientist Emeritus, is an outstanding researcher and breeder, author of 90 apple and pear cultivars, founder of a scientific school specializing on priority trends in pome fruit breeding: – development of adaptable triploid apple cultivars with regular fruiting, high marketability of fruits, and increased self-fertility; – development of apple cultivars immune or highly resistant to scab; – development of triploid apple cultivars with immunity to scab; – development of columnar apple cultivars for super-intensive orchards and main technology elements for their cultivation; – development of apple cultivars with improved biochemical composition of fruits with higher content of ascorbic acid (vitamin C) and Р-active substances (vitamin Р).